Parkinson’s Narratives: Onset Experiences and Perceived Benefits of Preferred Physical Activity - Burgess, Sandra; Rasmusson, Xeno (Advances in Social Sciences Research Journal, 2016)
Background: Parkinson’s disease (PD) is a relatively common brain-based movement disorder and there are many experimental studies illustrating the wide ranging effects of activity therapy in PD patients. Purpose: This narrative study addresses two key research questions; how do persons with Parkinson’s disease (PD) experience loss of physical activity? And, second, what experiences have persons with PD had with dance and/or movement therapy in managing their symptoms? Method: Four anonymous voluntary participants (two men and two women) ranging in age from 61-90 years old suffering from mild to severe Parkinson’s were recruited. In-depth interviews were used in order to gather each participant’s unique story. At a follow-up meeting, participants had a chance to review, correct or add to their stories and selected an alias to protect their identity. Results: Four sub-questions and eight themes emerged from the participants’ narratives: These were: 1) Symptom discovery during activity and the emotional responses to the discovery. 2) Curtailing their favorite activities and identifying the importance of the activity before PD. 3) Involvement with different movement therapies, and activity therapy was suggested by friends, family or physicians. 4) Exercise helps PD patients experience joy and also helps functional mobility. Discussion: This study provides insights into the direct experiences of PD patients with loss of activity and exercise-based movement therapies. These results add to the prior experimental studies reporting that exercise with movement therapies is effective for helping PD patients with their symptoms, and that is that they are also enjoyable and acceptable to them.